2006
DOI: 10.1021/ja054070n
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Interactions of Water-Soluble Porphyrins with RNA Duplexes

Abstract: We characterized the interactions of meso-tetrakis(4N-(2-hydroxyethyl)pyridinium-4-yl) porphyrin (TEtOHPyP4), meso-tetrakis(4N-allylpyridinium-4-yl) porphyrin (TAlPyP4), and meso-tetrakis(4N-metallylpyridinium-4-yl) porphyrin (TMetAlPyP4) with the poly(rA)poly(rU) and poly(rI)poly(rC) RNA duplexes between 18 and 45 degrees C by employing circular dichroism, light absorption, and fluorescence intensity spectroscopic measurements. Our results suggest that TEtOHPyP4 and TAlPyP4 intercalate into the poly(rA)poly(r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 27 publications
7
38
0
Order By: Relevance
“…Outside binding without stacking is demonstrated by a small red shift (about 6-8 nm) and hypochromicity (10%) or even hyperchromicity of the soret band. Outside binding with stacking is indicated by variable effects on the soret band [21][22][23]. Accordingly, for both forms of DNA, the changes of the first and the second stages are intermediate between those expected for intercalative and outside binding modes.…”
Section: Resultsmentioning
confidence: 94%
“…Outside binding without stacking is demonstrated by a small red shift (about 6-8 nm) and hypochromicity (10%) or even hyperchromicity of the soret band. Outside binding with stacking is indicated by variable effects on the soret band [21][22][23]. Accordingly, for both forms of DNA, the changes of the first and the second stages are intermediate between those expected for intercalative and outside binding modes.…”
Section: Resultsmentioning
confidence: 94%
“…Our previous studies of interaction of water soluble meso-tetra-(4N-oxyethylpyridyl) porphyrin and its Cu(II)-and Co(II)-containing derivatives (CuTOEPyP4 and CoTOEPyP4) with B-DNA of calf thymus have shown that at high ionic strengths TOEPyP4 and CuTOEPyP4 prefer the intercalative binding mechanism, and CoTOEPyP4, which has an axial ligand, binds only externally in the major groove of DNA [17][18][19]. In this paper, the comparative study of interaction of these porphyrins with A-and Bform DNA at low ionic conditions is conducted.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous works we have characterized the binding of four novel water soluble porphyrins to nucleic RNA duplexes [5][6][7][8] . We estimated their binding modes and binding thermodynamics.…”
Section: Resultsmentioning
confidence: 99%
“…The concentrations of double-stranded polynucleotides were determined spectroscopically using molar extinction coefficients presented in our pervious papers 5,6 . All spectroscopic measurements were performed in 0.1 BPSE buffer (1BPSE = 6 mM Na 2 HPO 4 + 2 mM NaH 2 PO 4 + 185 mM NaCl + 1 mM Na 2 EDTA), pH 7.0, µ = 0.02.…”
Section: Mesomentioning
confidence: 99%
See 1 more Smart Citation